2006
DOI: 10.1002/ardp.200600016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β‐Hydroxypropanoic Acid Derivatives as Potential Anti‐inflammatory, Analgesic and Antimicrobial Agents

Abstract: A series of new 3-(substituted) 3-hydroxy-propanoic acid ethyl esters 1a-c, hydrazides 2a-c, thiosemicarbazides 3a-f, and semicarbazides 3g, 3h has been synthesized. Cyclization of compounds 3a-d in basic medium yielded 1,2,4-triazole-5-thiones 4a-d. On the other hand, reaction of hydrazides 2a-c with CS(2 )in basic medium afforded 1,3,4-oxadiazole-5-thiones 5a-c. All the synthesized compounds were characterized by their physical and spectral analyses data. The newly synthesized compounds were evaluated for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…On the basis of such data, it is not unreasonable to conclude that the studied reactions are completely regioselective and accordingly 1,3,4-oxadiazole 5 is isolated as the sole product by reaction of hydrazide 3 with carbon disulfide, whereas the alternative site of cyclization to the corresponding thienopyrimidinone 4 results from the reaction of compound 3 with thiourea. This observation is in complete agreement with previous literature reports on the wellestablished formation of 1,3,4-oxadiazoles by heating hydrazides with carbon disulfide in the presence of bases [28][29][30].…”
Section: Chemistrysupporting
confidence: 93%
“…On the basis of such data, it is not unreasonable to conclude that the studied reactions are completely regioselective and accordingly 1,3,4-oxadiazole 5 is isolated as the sole product by reaction of hydrazide 3 with carbon disulfide, whereas the alternative site of cyclization to the corresponding thienopyrimidinone 4 results from the reaction of compound 3 with thiourea. This observation is in complete agreement with previous literature reports on the wellestablished formation of 1,3,4-oxadiazoles by heating hydrazides with carbon disulfide in the presence of bases [28][29][30].…”
Section: Chemistrysupporting
confidence: 93%
“…Exploration of the 1,3-thiazolidin-4-ones showed that the tibacterial activity not only depended on the 1,3-thiazolidin-4-one pharmacophore, but also on th ture and position of its substituents; for example, electron withdrawing group substitutions o omatic rings of biphenyl-4-thiazolidinone derivatives showed improved antibacterial activity [11 umerous new derivatives with the pharmacophoric 4-thiazolidinone ring were substituted wit e-membered heterocyclic rings, [12] such as thiadiazole, [13] thiazoles [14] or 1,2,4-triazoles [15 seen in Figure 2. Moreover, 1,2,4-triazoles are core structures in medicinal chemistry research wi verse biological activities [16][17][18]. The SAR of the antibacterial activity of the 1,3-thiazolidin-4-one scaffold has become the subject of intense research projects [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous new derivatives with the pharmacophoric 4-thiazolidinone ring were substituted with five-membered heterocyclic rings, [12] such as thiadiazole, [13] thiazoles [14] or 1,2,4-triazoles [15], as seen in Figure 2. Moreover, 1,2,4-triazoles are core structures in medicinal chemistry research with diverse biological activities [16][17][18]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, chiral β-hydroxycarboxylic acids are important intermediates widely used as chiral precursors of anti-inflammatory products, [87] β-amino acids, [88] β-lactams, [89] β-lactones, [90] and pheromones [91].…”
Section: Brønsted-base-mediated Carboxylation Of C(sp 3 )-H Bonds Witmentioning
confidence: 99%